1985
DOI: 10.1111/j.1445-5994.1985.tb02742.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hypothyroidism and Essential Hypernatremia in a Patient With Histiocytosis X

Abstract: A 27 year old woman with histiocytosis X had an unusual initial presentation with features of primary hypothyroidism and a goitre. Diagnosis was made by lung and thyroid biopsies. Endocrine tests showed the presence of hypopituitarism and a discrete suprasellar mass, consistent with hypothalamic histiocytosis X, was demonstrated by computerised tomography. Radiotherapy and chemotherapy arrested the clinical progression of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The diagnosis of thyroidal malignant histiocytosis of Langerhans' cell type, however, was not made until pathological examination of the surgical specimen revealed the proliferation of Langerhans' cells in the thyroid, since repeated fine needle aspiration biopsies were interpreted as papillary thyroid carcinoma and failed to confirm the presence of Langerhans' cells in the thyroid. Histiocytes were also not detected by needle aspiration cytology in the case reported by Ma et al (1985). In addition, other investigators have indicated similar difficulty in differentiating between Langerhans' cell histiocytosis of the thyroid and thyroid carcinoma (Coode & Shaikh, 1988;Goldstein & Layfield, 1991;Lai et al, 1992;Ho et al, 1993) or inflammatory disease such as subacute thyroiditis (Lahey et al, 1986) on the basis of analysis of fine needle aspiration biopsy.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The diagnosis of thyroidal malignant histiocytosis of Langerhans' cell type, however, was not made until pathological examination of the surgical specimen revealed the proliferation of Langerhans' cells in the thyroid, since repeated fine needle aspiration biopsies were interpreted as papillary thyroid carcinoma and failed to confirm the presence of Langerhans' cells in the thyroid. Histiocytes were also not detected by needle aspiration cytology in the case reported by Ma et al (1985). In addition, other investigators have indicated similar difficulty in differentiating between Langerhans' cell histiocytosis of the thyroid and thyroid carcinoma (Coode & Shaikh, 1988;Goldstein & Layfield, 1991;Lai et al, 1992;Ho et al, 1993) or inflammatory disease such as subacute thyroiditis (Lahey et al, 1986) on the basis of analysis of fine needle aspiration biopsy.…”
Section: Discussionmentioning
confidence: 79%
“…Langerhans' cell histiocytosis of the thyroid is an extremely rare disease, and fewer than 20 cases have been reported previously (Whitaker et al, 1971;Teja et al, 1981;Ma et al, 1985;Lahey et al, 1986;Sinisi et al, 1986;Coode & Shaikh, 1988;Goldstein & Layfield, 1991;Gaines et al, 1991;Schofield et al, 1992;Manna et al, 1992;Lai et al, 1992;Ho et al, 1993). Primarily young people (age range 21 months to 36 years) have been affected, and our patient is the oldest recorded, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…So far, to the best of our knowledge, only seven cases have been reported; FNAC was done in only three cases. [2][3][4] Kirchgraber et al 3 reported a case of a 16-year-old male who presented with persistent, diffuse enlargement of the thyroid gland along with a history of a pituitary tumor. FNAC smears showed a large number of LCs, eosinophils and follicular cells.…”
Section: Discussionmentioning
confidence: 99%
“…Solitary involvement of the thyroid by LCH is uncommon, and histology of only a few cases has been reported. 1,2,4,5 Fine needle aspiration cytology (FNAC) of LCH has rarely been described. 2,3 This paper reports the detailed cytologic features of a histology-proved case of LCH of the thyroid.…”
mentioning
confidence: 99%
“…In one of these cases, a diagnosis of PTC in a background suggestive of LCH was rendered [15]. In the other reported cases of thyroid LCH where FNA was performed, the cytologic findings were misinterpreted as ''atypical follicular epithelial cells'', ''epithelial neoplasm'' and papillary or medullary carcinoma, or were non-diagnostic [6,25]. Therefore, a high index of suspicion is required to correctly diagnose LCH in thyroid FNA specimens.…”
Section: Fine Needle Aspiration and Biopsymentioning
confidence: 99%